A tale of two stones in nose - Sreenath, Sarada; Sasidharan, Saji; George, Elizabeth Thottathikunnath; George, Saju Kuttiplakal (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Rhinolith is stone formation in nose. It is very rare. Here we discuss 2 cases of rhinoliths along with its management and review the literature. First is a case of giant rhinolith detected in a 41-year-old male patient and second is rhinolith in a 52-year-old lady with no known history of foreign body insertion. This article can enable the attending clinician to diagnose this still prevailing condition with high index of suspicion leading to its appropriate management.